Ensuring Clinical Readiness: Commissioning, Acceptance and Performance Testing of Closed Bore Linear Accelerator Compatible Surface Guided Radiotherapy System - Anand Jadhav; Ajinkya Gupte; Prasad Raj Dandekar; Sachin Rasal; Omkar Awate; Mayank Dhoundiyal (Journal of Medical Physics)
Introduction: Surface Guided Radiation Therapy (SGRT) enhances radiation therapy by providing real-time support without additional X-ray exposure. It ensures precise patient positioning, continuous monitoring, and motion management. However, closed-bore LINACs face optical line-of-sight challenges with ceiling-mounted SGRT systems. Objective: This study commissions the AlignRT InBore™ SGRT system on the Ethos™ LINAC at a Mumbai tertiary care center, evaluating accuracy, precision, reproducibility, and temporal stability. Methods: System Commissioning: 1) Acceptance tests per Vision RT’s Form 412: Camera calibration, setup validation, thermal stability, relative shift accuracy. Phantom measurements for performance assessment. 3) Deliberate rotational motion errors to test detection capability. Results: Comparison with Existing Systems: 1) Consistent with SGRT performance on Halcyon™ LINAC (Nguyen et al.). 2) Reliable mechanical and imaging test results. Patient-Specific QA: 1) 51 adaptive treatment sessions. 2) High gamma pass rates confirmed clinical efficacy. 3) Essential for Ethos™ LINAC, which lacks 6D couch correction. Conclusion: This study demonstrates successful SGRT integration with Ethos™, improving treatment accuracy, patient comfort, and efficiency in closed-bore LINACs, advancing radiation oncology in India.